2019
DOI: 10.1038/s41598-019-55018-9
|View full text |Cite
|
Sign up to set email alerts
|

Tidal amplification and salt intrusion in the Mekong Delta driven by anthropogenic sediment starvation

Abstract: Natural resources of the Mekong River are essential to livelihood of tens of millions of people. Previous studies highlighted that upstream hydro-infrastructure developments impact flow regime, sediment and nutrient transport, bed and bank stability, fish productivity, biodiversity and biology of the basin. Here, we show that tidal amplification and saline water intrusion in the Mekong Delta develop with alarming paces. While offshore M2 tidal amplitude increases by 1.2–2 mm yr−1 due to sea level rise, tidal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 54 publications
8
126
1
1
Order By: Relevance
“…Although part of the future extraction-induced subsidence in inevitable (Scenario M4), a large part still can still be mitigated and avoided. A strong reduction in groundwater extraction would not only allow the aquifer system to recharge, and subsequently decrease aquifer system compaction, it would also reduce other water-related issues, such as salt water intrusion in the aquifer system and decrease in water quality (Renaud et al 2015, Smajgl et al 2015, Eslami et al 2019. Although the best solution to reduce extraction-induced subsidence is to immediately stop all groundwater extraction, this is realistically not an option, as people in the delta rely on groundwater for their freshwater supply.…”
Section: Future Of the Mekong Deltamentioning
confidence: 99%
See 1 more Smart Citation
“…Although part of the future extraction-induced subsidence in inevitable (Scenario M4), a large part still can still be mitigated and avoided. A strong reduction in groundwater extraction would not only allow the aquifer system to recharge, and subsequently decrease aquifer system compaction, it would also reduce other water-related issues, such as salt water intrusion in the aquifer system and decrease in water quality (Renaud et al 2015, Smajgl et al 2015, Eslami et al 2019. Although the best solution to reduce extraction-induced subsidence is to immediately stop all groundwater extraction, this is realistically not an option, as people in the delta rely on groundwater for their freshwater supply.…”
Section: Future Of the Mekong Deltamentioning
confidence: 99%
“…The world's third largest delta, the populous and low-lying Mekong delta in Vietnam is facing increased river flooding (Renaud et al 2015, Smajgl et al 2015, Eslami et al 2019. On top of that, like many other deltas in the world (Syvitski et al 2009, Nicholls andCazenave 2010), the Mekong delta experiences accelerating rates of relative sea-level rise, the combined effect of absolute sea-level rise and land subsidence.…”
Section: Introductionmentioning
confidence: 99%
“…Should channel bed lowering continue unmitigated, tidal extent in the Mekong delta will increase by ~56 km in the next two decades. This dramatic landward migration of the tidal limit risks causing a collapse of ecosystem services, threatening food security, via exacerbation of saline intrusion 4,26 . Tidal extension also affects delta channel stability and flood risk because of changes in bifurcation function and water and sediment routing 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The combined influence of these compounded pressures of relative sea-level rise and changes in water and sediment discharges, driven by global warming 24 and catchment engineering 25 , directly effects the sensitive balance between fluvial and tidal forces that governs tidal extent in large deltas. This is important because the tidal extent regulates saline intrusion 26 , water and sediment routing 27 , and channel stability 28 . Yet, the relative impacts of the distinct pressures influencing tidal extent have not been quantified, hampering evidence-based policy to underpin adaptation and mitigation strategies.…”
Section: Here We Use New Field Data and Hydrodynamic Modelling To Quamentioning
confidence: 99%
“…One of the large drivers of the subsidence rates presently experienced, was the steady increase in groundwater extraction since the 90's from its thick, locally over 500 m, multi-aquifer system (Minderhoud et al, 2017). As new elevation data revealed that the deltas elevation relative to local sea level is even lower than previously assumed (on average the delta plain is elevated only ∼ 80 cm above local sea level) (Minderhoud et al, 2019), the accelerating subsidence rates strongly increase the vulnerability to sea-level rise-induced flooding, salinization (Eslami et al, 2019), coastal erosion and, ultimately, threaten the livelihood of 18 million delta inhabitants with permanent inundation (Minderhoud et al, 2020).…”
Section: Causes Of Land Subsidence In Deltasmentioning
confidence: 97%